Careful Blasting in Greenland A Case Story of 4 Major Blasting Projects 1986-88 - Erik K. Lauritzen; Jorgen Schneider; Niels Madsen (International Society of Explosives Engineers, 1989)
From 1986 to 1988 Kalaallit Tunisassiorfiat (KTU)/Gronlands Hjemmestyres Produktionsvirksomhed (the part of Greenland's own governing body which is in charge of production activities) has been responsible for blasting projects in the following 4 towns: Ilulissat/Jakobshavn, Qasigiannguit/ Christianshab, Qeqertarsuaq/Godhavn, Sisimiut/Holsteinsborg